Implementation of Victims' Rights in District Court Decisions: A Study of Legal Protection for Victims of Domestic Violence - Kevin Endilosa Barus; Novelina Mutiara; Elpina (Academic Solution Publisher, 2024)
This study aims to identify factors that trigger domestic violence (DV) by husbands against their wives. Some of the main factors include the patriarchal system, discrepancies in husband's expectations, economic competition in the household, and husband's frustration that leads to physical, sexual, psychological violence, or family neglect. In addition, women's limited access to the legal process is also an obstacle, where the Criminal Procedure Code minimally addresses victims' rights, and reports are often considered as ordinary domestic conflicts. This research also examines legal protection for victims of domestic violence based on Law No. 23 of 2004 and how the district court provides protection for victims in its decisions. The research used a normative juridical method with a statutory and case approach, as well as literature study techniques to collect data. The results showed that the judge's decision still focused on punishment for the perpetrator, without considering the victim's right to compensation either through restitution or compensation. Decisions tend to only follow the provisions of the written law without including aspects of recovery for victims in the criminal justice system in Indonesia..